2016
DOI: 10.1007/s10459-016-9729-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between extracurricular activities assessed during selection and during medical school and performance

Abstract: Several medical schools include candidates' extracurricular activities in their selection procedure, with promising results regarding their predictive value for achievement during the clinical years of medical school. This study aims to reveal whether the better achievement in clinical training of students selected on the basis of their extracurricular activities could be explained by persistent participation in extracurricular activities during medical school (msECAs). Lottery-admitted and selected student ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
3
17
0
3
Order By: Relevance
“…It should be noted, however, that this study did not look at differences in clinical performance between the three groups. In our most recent study we found that students selected on the basis of their puECAs persisted in their ECAs during medical school and that this persistent participation was related to better clinical performance, which further supports the inclusion of puECAs in the selection procedure …”
Section: Non‐grades‐based Selection In the Netherlandssupporting
confidence: 58%
See 1 more Smart Citation
“…It should be noted, however, that this study did not look at differences in clinical performance between the three groups. In our most recent study we found that students selected on the basis of their puECAs persisted in their ECAs during medical school and that this persistent participation was related to better clinical performance, which further supports the inclusion of puECAs in the selection procedure …”
Section: Non‐grades‐based Selection In the Netherlandssupporting
confidence: 58%
“…In our most recent study we found that students selected on the basis of their puECAs persisted in their ECAs during medical school and that this persistent participation was related to better clinical performance, which further supports the inclusion of puECAs in the selection procedure. 41 It is good to note that although puECAs can be seen as a form of personal statements, 17 their assessment, at least in the Dutch medical schools, is different from analysing the content of free response personal statements, as for example described by Ferguson et al 42 The use of a highly structured application form in combination with a highly structured rating form provides a high degree of structure to the raters' judgements. This may positively affect the criterion-related validity, in the same way as job interviews are positively affected by the degree of structure.…”
Section: A Participation Effect?mentioning
confidence: 99%
“…The predictive validity of SSGPA, ACS, and NCS was, as expected, confirmed by a comparison of Signal Detection analyses and correlational analyses in a previous study (van Ooijen-van der Linden et al, 2017) and the regression analyses matching the Signal Detection analyses for the data in this study are presented in Online Resource 1. A summary of the data collection and Signal Detection approach used in this study, a specification of b and d in Figure 1 for this study, is depicted in Figure 2.…”
Section: Successful and Unsuccessful Students And Admission Toolssupporting
confidence: 86%
“…Research into predictors other than secondary school grade point average (SSGPA)-which is far from accurate-is still work in progress, and a "gold standard" has not yet been conceived (Richardson et al, 2012;Schripsema et al, 2014Schripsema et al, , 2017Shulruf and Shaw, 2015;Makransky et al, 2016;Patterson et al, 2016;Pau et al, 2016;Sladek et al, 2016;Yhnell et al, 2016;Wouters et al, 2017). Program-and institution specific work samples appear promising valuable predictors of academic achievement in addition to past academic achievement (Niessen et al, 2016;Stegers-Jager, 2017;van Ooijen-van der Linden et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation